Current State of Antimicrobial Stewardship in Children's Hospital Emergency Departments. (8th February 2017) - Mistry, Rakesh D.; Newland, Jason G.; Gerber, Jeffrey S.; Hersh, Adam L.; May, Larissa; Perman, Sarah M.; Kuppermann, Nathan; Dayan, Peter S.
Abstract : BACKGROUND: Antimicrobial stewardship programs (ASPs) effectively optimize antibiotic use for inpatients; however, the extent of emergency department (ED) involvement in ASPs has not been described. OBJECTIVE: To determine current ED involvement in children's hospital ASPs and to assess beliefs and preferred methods of implementation for ED-based ASPs. METHODS: A cross-sectional survey of 37 children's hospitals participating in the Sharing Antimicrobial Resistance Practices collaboration was conducted. Surveys were distributed to ASP leaders and ED medical directors at each institution. Items assessed included beliefs regarding ED antibiotic prescribing, ED prescribing resources, ASP methods used in the ED such as clinical decision support and clinical care guidelines, ED participation in ASP activities, and preferred methods for ED-based ASP implementation. RESULTS: A total of 36 ASP leaders (97.3%) and 32 ED directors (86.5%) responded; the overall response rate was 91.9%. Most ASP leaders (97.8%) and ED directors (93.7%) agreed that creation of ED-based ASPs was necessary. ED resources for antibiotic prescribing were obtained via the Internet or electronic health records (EHRs) for 29 hospitals (81.3%). The main ASP activities for the ED included production of antibiograms (77.8%) and creation of clinical care guidelines for pneumonia (83.3%). The ED was represented on 3 hospital ASP committees (8.3%). No hospital ASPs actively monitored outpatient ED prescribing. Most ASP leaders (77.8%) and ED directors (81.3%) preferred implementation of ED-based ASPs using clinical decision support integrated into the EHR. CONCLUSIONS: Although ED involvement in ASPs is limited, both ASP and ED leaders believe that ED-based ASPs are necessary. Many children's hospitals have the capability to implement ED-based ASPs via the preferred method: EHR clinical decision support. Infect Control Hosp Epidemiol 2017;38:469–475